Fugitive Teacher Education: Nurturing Pedagogical Possibilities in Early Childhood Education. Issue 3 (3rd July 2019) - Lees, Anna; Vélez, Verónica N.
Abstract: This article argues for the necessity of fugitivity in teacher education to interrupt and subvert the current regime of standardization in public education. Centering the voices of teachers and teacher candidates, this qualitative case study explores the importance of unsanctioned spaces for destabilizing co-optations of multiculturalism and social justice in teacher education. Findings suggest conceptual and practical possibilities for developing critical curricula and pedagogies in early childhood teacher education that work towards a postcolonial state.